x-7.6=-6.5

Simple and best practice solution for x-7.6=-6.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-7.6=-6.5 equation:


Simplifying
x + -7.6 = -6.5

Reorder the terms:
-7.6 + x = -6.5

Solving
-7.6 + x = -6.5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7.6' to each side of the equation.
-7.6 + 7.6 + x = -6.5 + 7.6

Combine like terms: -7.6 + 7.6 = 0.0
0.0 + x = -6.5 + 7.6
x = -6.5 + 7.6

Combine like terms: -6.5 + 7.6 = 1.1
x = 1.1

Simplifying
x = 1.1

See similar equations:

| 12=-24y | | 4x+40=13x-68 | | r+33=14 | | -2t^2-6t+5=0 | | 5y-2+y+48=5y+50-1y | | 5x=165 | | 6x+34=14x+30 | | 3x+139=2x+26 | | y+25y-15y-9y=15-15 | | 2S=2Vt-gt^2 | | 5+x=(3+19x) | | 31+3x=34 | | 6x^2+4x=240 | | 9x+15-7x+15=-2 | | -113=5(5p+3)-3 | | s-44=-13 | | -4(x+5)+3=6(x+4)+1 | | f/2-19=-17 | | 8x-12=68 | | 6q=-6+7q | | 8x=6x+14 | | 5.85=0.65x | | -8=-(v+4) | | -7+6r=6r+3+r | | 8x-(x+3)(4x-5)=(5+2x)(4-x)-3(x+4) | | 6(8+3x)=174 | | 6y-25=4y+2 | | 17-9x=11+7x | | 69-7x=2x+23 | | h(t)=-16x^2+14 | | -160=8(4m-4) | | 9-7x=113-35x |

Equations solver categories